Diversity Is Only Skin-Deep: Intercultural Inclusion in Ontario FSL Classrooms - Abdulla, Rosanne (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2025)
Despite growing demographic diversity among French-speaking newcomers to Canada, as well as recent curricular changes at the provincial level, many French as a Second Language (FSL) classrooms in Ontario remain grounded in Eurocentric norms. This article explores superficial gestures of inclusion in the classroom that mask deeper systemic exclusion, thus hindering the success of underrepresented students. We examine how current institutional paradigms and pedagogical practices tend to tokenize non-European voices, romanticize the notion of la Francophonie, and reinforce colonial hierarchies of power. In response, we propose practical strategies and critical frameworks to support educators in moving beyond performative diversity toward meaningful, anti-oppressive inclusion. By centering collective educator self-reflection and a fundamental reimagining of French language education, the piece invites Ontario educators and policymakers to re-envision the FSL classroom as a transformative, intercultural space rooted in critical inquiry, plurilingual identity affirmation, and global equity.